Public Expenditure and Economic Growth of Nepal - Dangal, Dil Nath; Gajurel, Ram Prasad (Rupantaran: A Multidisciplinary Journal, 2021)
This study intended to evaluate the trends of public expenditure and to show the relationship between public expenditure and economic growth in Nepal. In order to fulfill these objectives, the chart, correlation, and regression were employed by using time series data sets over the period of 1974/75 to 20108/19. Economic growth (RGDP) (proxied as the real GDP with rebasing 2009/10) as dependent variable and recurrent expenditure (RE), capital expenditure (CE), expenditure on education (EE), expenditure on health (HE), and expenditure on transportation and communication (TCE) were proxied as public expenditure. The study revealed that there is positive correlation between dependent and predictors. The results of regression also confirmed that there is positive relationship between public expenditure on economic growth of Nepal. Particularly, HE and TCE had negative relationship with RGDP. This study applied 45 annually observed times series data sets and mainly fitted regression model to examine the relationship between public expenditure and economic growth in Nepal. The main policy implication of this study is that government and concern body should give more concern about capital expenditure for enhancing productive activities and attention about recurrent expenditure. Also, education, health, and transportation and communication are the economic infrastructure, so government should most attention to increase expenditure on these sectors that may produce long-run impact on economy.